2015
DOI: 10.1016/j.cell.2015.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Timing of CFTR Pore Opening and Structure of Its Transition State

Abstract: In CFTR, the chloride ion channel mutated in cystic fibrosis (CF) patients, pore opening is coupled to ATP-binding-induced dimerization of two cytosolic nucleotide binding domains (NBDs) and closure to dimer disruption following ATP hydrolysis. CFTR opening rate, unusually slow because of its high-energy transition state, is further slowed by CF mutation ΔF508. Here, we exploit equilibrium gating of hydrolysis-deficient CFTR mutant D1370N and apply rate-equilibrium free-energy relationship analysis to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 70 publications
5
71
0
Order By: Relevance
“…Based on our data we cannot rule out that the extracellular gate possibly covers a conformational ensemble between outward-occluded and outward-facing states. A recent biophysical study of CFTR elucidated a conformational progression of channel opening with the following sequence of events: NBD closure, propagation of the conformational change to the intracellular part of the TMDs and finally the opening of the extracellular gate (Sorum et al, 2015). The functional importance of extracellular gate opening in the context of substrate transport remains elusive and studying the effects of substrates or point mutations in the transporter will help to elucidate this intriguing aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data we cannot rule out that the extracellular gate possibly covers a conformational ensemble between outward-occluded and outward-facing states. A recent biophysical study of CFTR elucidated a conformational progression of channel opening with the following sequence of events: NBD closure, propagation of the conformational change to the intracellular part of the TMDs and finally the opening of the extracellular gate (Sorum et al, 2015). The functional importance of extracellular gate opening in the context of substrate transport remains elusive and studying the effects of substrates or point mutations in the transporter will help to elucidate this intriguing aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The combinations of mutations that were best for stabilizing NBD1, 6SS and 7SS, increased T m func from 22 °C for WT CFTR to 36 °C (Table 1). ATP binding and hydrolysis in CFTR, as in all ABC transporters, depends on the two NBDs interacting in a head-to-tail dimer to sandwich two MgATP molecules between the Walker A/B motifs of one NBD and the Signature motif of the other [32,66,67]. CFTR NBD1 has a degenerate Walker B motif and lacks the switch histidine (equivalent to H1402), making this composite site inactive [17,68].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence from our group demonstrated that inhibition of CFTR affects HCO 3 -uptake resulting in low PKA activity and inhibition of cAMP/PKA-downstream events such as the increase in tyrosine phosphorylation, hyperactivated motility and acrosome reaction (9). It is well established in several systems that CFTR phosphorylation by PKA is required for its activation (15)(16)(17). For this reason, we postulated that an initial increase in PKA activity is necessary to activate CFTR channels and produce a sustained increase in HCO 3 -and cAMP.…”
Section: Introductionmentioning
confidence: 99%